PENGARUH INOVASI TERHADAP MINAT BERWIRAUSAHA MASYARAKAT DESA EWO KECAMATAN LOLOMATUA - Albert Ndruru (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
This research aims to determine the influence of innovation on the entrepreneurial interest of the people of Ewo Village, Lolomatua District. This type of research is causal quantitative research. The sample in this study amounted to 32 people. The analytical method used in this research is simple linear regression analysis. The results of this research show that there is an influence of innovation on the entrepreneurial interest of the people of Ewo Village, Lolomatua District. The results of this research show that there is an influence of innovation on the entrepreneurial interest of the people of Ewo Village, Lolomatua District, this can be proven by the value of tcount (4.402) > ttable (1.549). The suggestion in this research is that to become an entrepreneur, people must have entrepreneurial innovation or the inner will to do entrepreneurship and have an interest in entrepreneurship themselves without being forced by others.